Sorafenib versus Transarterial chemoembolization for advanced-stage hepatocellular carcinoma: a cost-effectiveness analysis - Chen, Shuling (BMC Cancer, 2018)
BACKGROUND: Sorafenib and transarterial chemoembolization (TACE) might both provide survival benefit for advanced hepatocellular carcinoma (HCC). Adopting either as a first-line therapy carries major cost and resource implications. We aimed to estimate the cost-effectiveness of sorafenib and TACE in advanced HCC. METHODS: A Markov model was constructed in a hypothetical cohort of patients aged 60 years with advanced HCC and Child-Pugh A/B cirrhosis over a 2-year time frame. Three strategies (full or dose-adjusted sorafenib and TACE) were compared in two cost settings: China and the USA. Transition probabilities, utility and costs were extracted from systematic review of 27 articles. Sensitivity analysis and Monte Carlo analysis were conducted. RESULTS: Full and dose-adjusted sorafenib respectively produced 0.435 and 0.482 quality-adjusted life years (QALYs) while TACE produced 0.375 QALYs. The incremental cost-effectiveness ratio (ICER) of full-dose sorafenib versus TACE was $101,028.83/QALY in China whereas full-dose sorafenib is a dominant strategy (ICER of -$1,014,507.20/ QALY) compared with TACE in the USA. Compared to full-dose sorafenib, dose-adjusted sorafenib was the dominant strategy with the negative ICERs in both China (−$132,238.94/QALY) and the USA (−$230,058.09/QALY). However, dose-adjusted sorafenib is not available currently, so full-dose sorafenib should be compared with TACE. As the acceptability curves shown, full-dose sorafenib was the optimal strategy at the accepted thresholds of WTP in these two countries. Specifically, full-dose sorafenib was the cost-effective treatment compared with TACE if a WTP was set above $21,670 in the USA, whereas in China, TACE could be more favorable than full-dose sorafenib if a WTP was set below $10,473. CONCLUSIONS: Dose-adjusted sorafenib may be cost-effective compared to full-dose sorafenib or TACE for advanced HCC patients. However, when confining the comparisons between full-dose sorafenib and TACE, full-dose sorafenib was cost-effective for these patients, under the accepted thresholds of WTP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4308-7) contains supplementary material, which is available to authorized users.